PENERAPAN MODEL EXPERIENTIAL LEARNING PADA MATA PELAJARAN PENATAAN PRODUK UNTUK MENINGKATKAN PEMAHAMAN SISWA KELAS XII BDP 2 SMKN 02 SELONG - Esty Rahayu Ningsih (LPPM Institut Pendidikan Nusantara Global, 2022)
This research aims to implementing experiential learning model in product arrangement subject to improve students’ understanding of class XII BDP 2 SMKN 02 Selong. This research is an action research in classroom. The result of this reaserch showed that implementing experiential learing model on product arrangement subject can improve the students’ understanding. This has been seen from the increase in student evaluation test results where at the pre-action stage 46.88% of students achieve the KKM score with an average value of 74.09 then increased to 77.16 after first cycle of action and again increased to 80.66 after the second cycle of action. In addition, in first cycle 90.63% of students managed to achieve scores above the KKM and in the second cycle 100% of students managed to achieve scores above KKM The conclution of this research is implementation of experiential learning model on product arrangement subject can improve students’ understanding of class XII BDP 2 SMKN 02 Selong